A Review of the Effects of Bioactive Compounds in Aged Black Garlic on Human Health Issues - Reena Devi; Suchitra Nishal; Davinder Kumar; Virender Kumar; Naveen Khatri (Current Functional Foods, 2026)
Garlic (Allium sativum) has been used by humans as both food and medicine since the ancient era. However, due to its strong flavor and odor, some people are reluctant to consume raw garlic. To reduce these characteristics, various garlic formulations have been developed. Aged black garlic (AGB) is one such form, characterized by a bittersweet flavor, jelly-like consistency, and the absence of a pungent odor. One of the bioactive components of ABG is Sallylcysteine, followed by S-allylmercaptocysteine, flavonoids, phenols, thiosulfate, and pyruvate. Fresh garlic is fermented at regulated high temperatures (60°C–90°C) and humidity (80– 90%) to produce black garlic. Due to the Maillard process, also known as the non-enzymatic browning reaction, the garlic turns dark brown during aging. Recent research has confirmed that AGB, along with its bioactive composites assorted biological as well as pharmacological responses, including anti-cancer, anti-inflammatory, anti-obesity, hepatoprotection, hypolipidemia, cardiovascular protection, anti-inflammatory effect, anti-diabetic, traumatic brain injury, and anti-Alzheimer's disease activities. This study provides an overview of the current understanding of biological mechanisms, physical and chemical characteristics, side effects, and general restrictions of AGB.